2022
DOI: 10.1037/apl0000874
|View full text |Cite
|
Sign up to set email alerts
|

How employees’ voice helps teams remain resilient in the face of exogenous change.

Abstract: Teams often confront exogenous events that induce discontinuous change and unsettle existing routines. In the immediate aftermath of such events (the disruption stage), teams experience a dip in their performance and only over time regain their previous performance levels (in the recovery stage). We argue that prohibitive voice that allows teams to manage errors better is instrumental for preventing performance losses in the disruption stage. Whereas, promotive voice that helps teams innovate or improve team p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…In recent years, the voice literature has started to recognize that to sustainably motivate voice, employees need to be properly rewarded for speaking up. For instance, in a recent field intervention (Li & Tangirala, 2021b), scholars have demonstrated that providing adequate reward structures for voice (e.g., bonuses for expressing concerns or ideas) is an effective way of stimulating the behavior. As such, it is important to examine how managers go about rewarding employees who make the effort to speak up at work.…”
Section: Contributions To the Voice Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the voice literature has started to recognize that to sustainably motivate voice, employees need to be properly rewarded for speaking up. For instance, in a recent field intervention (Li & Tangirala, 2021b), scholars have demonstrated that providing adequate reward structures for voice (e.g., bonuses for expressing concerns or ideas) is an effective way of stimulating the behavior. As such, it is important to examine how managers go about rewarding employees who make the effort to speak up at work.…”
Section: Contributions To the Voice Literaturementioning
confidence: 99%
“…Given such benefits, it is potentially important for managers to reinforce voice by properly rewarding it (see Li & Tangirala, 2021b). However, managers often vary in how they respond to voice (Burris, 2012; Fast et al, 2014; Sherf et al, 2019).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research also demonstrates the importance of team communication for shaping team resilience, such as by generating new ideas and creating alignment within the team ( Carmeli et al, 2013 ; Gomes, Borges, Huber, & Carvalho, 2014 ). More recently, Li and Tangirala (forthcoming) found that team promotive and prohibitive voice, proximal outcomes of voice climate ( Frazier & Bowler, 2015 ; Morrison et al, 2011 ), enable process innovation (resource acquisition) and error management (resource protection) in response to major organizational change events. Altogether, prior research suggests that voice climate is a central mechanism for building team resilience capacity.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Voice is the act of speaking up with ideas, suggestions, or concerns to improve the workplace (Morrison, 2011) and is considered critical to the performance of workgroups (Detert et al, 2013;MacKenzie et al, 2011;McClean et al, 2013;Li & Tangirala, 2021;Liang et al, 2019). Yet, with some employees voicing more often than others (Morrison, 2011(Morrison, , 2014, scholars have sought to better understand the factors that affect speaking up.…”
mentioning
confidence: 99%